STUDI HADIS TENTANG SOLUSI PERMASALAHAN DEMOGRAFI DI NEGARA JEPANG DAN INDIA - Muhammad Saiful Khair; Nor Faridatunnisa; Munirah (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
As time goes by, the people’s number on earth is increasing. This phenomenon occurs because it is influenced by three main variables, birth, death and population movement. If one of them experiences a spike, then there is an uneven distribution of population and sometimes focused in one area. That is what is happening in Japan and India today. Both countries are experiencing population problems, both shortages and excesses, which result in social problems. This study aims to find solutions through the hadith’s perspective regarding the problems that occur in underpopulated countries, such as Japan, and overpopulated countries, such as India. By using thematic method in collecting data, and descriptive-analytic in the data processing, the results show that the Hadith of Muslim number 2610 can be a mediating solution for countries that are considered underpopulated like Japan, and overpopulated like India. The hadith refers to the Family Planning Program. This program is expected to be one of the solutions that can be implemented, because it still supports birth rate, but at the same time still pays attention to the distance limit or the number of births. Thus, the family planning program based on HR. Muslim Number 2610, can bring positive changes and a stable population for countries with serious demographic problems, such as Japan and India.